2002
DOI: 10.1007/s00468-002-0184-4
|View full text |Cite
|
Sign up to set email alerts
|

The greater seedling high-light tolerance of Quercus robur over Fagus sylvatica is linked to a greater physiological plasticity

Abstract: The responses of Quercus robur (oak) and Fagus sylvatica (beech) seedlings to four different light environments (full, 50%, 40% and 15% sunlight) and to a rapid increase in irradiance were explored during the summer, after 2 years of growth in a forest nursery at Nancy (France). Significant differences between the two species were found for most variables. Phenotypic plasticity for morphological variables (root-shoot ratio, leaf size, leaf weight ratio) was higher in beech than in oak, while the reverse was tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
127
3
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(163 citation statements)
references
References 52 publications
22
127
3
4
Order By: Relevance
“…Growth and survival of Fagus have been reported to increase with light availability in pine forests, but they reach an asymptote at 5 -10% of light (Kunstler et al, 2005), which is included in the first class of light (0 -25%) of this study. Decrease in recruitment at higher light levels can be related to either an increase in the abundance of herbs correlated to light levels at the plot scale and thus higher herbaceous competition (Kunstler et al, 2006), or to light inhibition (Valladares et al, 2002). Similarly, shrub cover has a positive effect on recruitment and this effect is particularly important in grassland, in agreement with previous studies (Rousset & Lepart, 2000;Kunstler et al, 2006) that have shown shrub facilitation on recruitment of trees in grassland because of protection against herbivores and indirect facilitation through a limitation of herb competition.…”
Section: Effect Of the Composition And Structure Of The Local Vegetationsupporting
confidence: 90%
“…Growth and survival of Fagus have been reported to increase with light availability in pine forests, but they reach an asymptote at 5 -10% of light (Kunstler et al, 2005), which is included in the first class of light (0 -25%) of this study. Decrease in recruitment at higher light levels can be related to either an increase in the abundance of herbs correlated to light levels at the plot scale and thus higher herbaceous competition (Kunstler et al, 2006), or to light inhibition (Valladares et al, 2002). Similarly, shrub cover has a positive effect on recruitment and this effect is particularly important in grassland, in agreement with previous studies (Rousset & Lepart, 2000;Kunstler et al, 2006) that have shown shrub facilitation on recruitment of trees in grassland because of protection against herbivores and indirect facilitation through a limitation of herb competition.…”
Section: Effect Of the Composition And Structure Of The Local Vegetationsupporting
confidence: 90%
“…The results of our study corroborate the previous evidence of greater physiological plasticity of shadeintolerant species (see Introduction). However, our results did not confirm a larger structural plasticity in shadetolerant species that has been hypothesized in some studies (Valladares et al 2002;Niinemets & Valladares 2004). In fact, the plasticity estimates based on the slopes of RGR vs. Ln(LAR) (structural plasticity) and RGR vs. Ln(NAR) (physiological variability) that merged both the light-and nutrient-dependent variation in LAR and NAR were positively associated (Fig.…”
Section:        contrasting
confidence: 87%
“…The previous suggestions of greater morphological plasticity in shade-tolerant species have been based on limited data (Valladares et al 2002;Niinemets & Valladares 2004). In fact, Valladares et al (2002) comparing structural and physiological attributes of Q. robur and Fagus sylvatica found that the more tolerant species F. sylvatica was morphologically more plastic. However, the data provided by Welander & Ottosson (1998) for the same two species suggest that the plasticity is similar if not larger in Q. robur.…”
Section:        mentioning
confidence: 99%
“…Many studies have used phenotypic plasticity indices to summarize the environmentally contingent trait expression of a given species, set of species or populations within a given species (Cheplick 1995;Poorter & Nagel 2000;Valladares et al 2000aValladares et al , 2002bValladares et al , 2005aBalaguer et al 2001;Gratani et al 2003) (see Table 1). Simple plasticity indices based on the mean phenotypes observed in each environment (e.g.…”
Section:           mentioning
confidence: 99%